Illegal Trade Competition and its Legal Consequences (Salam International Academic Journal, 2023)
Business or trade competition, encompassing both its legal and illegal aspects, is considered one of the most crucial and contentious topics within commercial law, benefiting individuals and societies in the contemporary era. Although the origins of business competition laws can be traced back to the United States approximately one and a half centuries ago with the enactment of the first such law, known as the Sherman Anti-trust Act, aimed at curbing trusts, in our country, Afghanistan, commercial law, specifically the Principles of Trade, was formally enacted during the reign of King Mohammad Zahir Shah in 1957 and includes rules regarding business competition. After the Bonn Agreement and the ratification of the new Constitution, the concept of a market economy has been embraced.In the framework of a market economy, governments possess the authority to intervene in the marketplace by enacting legislation designed to curb monopolistic practices and prevent any forms of anticompetitive behavior by suppliers of goods and services that may detrimentally impact consumers and society at large.This article endeavors to shed light on the significance and objectives of business competition, aiming to enhance awareness regarding this vital subject. To this end, the article will elucidate key concepts of business competition, explore both legal and illegal remedies and solutions, and discuss the punishment of illicit competitive practices.